2012
DOI: 10.1103/physrevlett.109.245506
|View full text |Cite
|
Sign up to set email alerts
|

Ductilizing Bulk Metallic Glass Composite by Tailoring Stacking Fault Energy

Abstract: Martensitic transformation was successfully introduced to bulk metallic glasses as the reinforcement micromechanism. In this Letter, it was found that the twinning property of the reinforcing crystals can be dramatically improved by reducing the stacking fault energy through microalloying, which effectively alters the electron charge density redistribution on the slipping plane. The enhanced twinning propensity promotes the martensitic transformation of the reinforcing austenite and, consequently, improves pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…Larger values of plasticity can be attained when the twinning propensity of the particles upon loading is favored. Wu et al 21 found that the capability of the B2-CuZr phase for deformation twinning could be tailored through microalloying with transition metals since they allow the tuning of the stacking fault energy of the primary slip system of B2-CuZr phase. The purpose of microalloying is to reduce the stacking fault energy of the primary slip system of reinforcing crystals to improve the twinning propensity thus favoring the martensitic transformation.…”
Section: Metallic Glass Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger values of plasticity can be attained when the twinning propensity of the particles upon loading is favored. Wu et al 21 found that the capability of the B2-CuZr phase for deformation twinning could be tailored through microalloying with transition metals since they allow the tuning of the stacking fault energy of the primary slip system of B2-CuZr phase. The purpose of microalloying is to reduce the stacking fault energy of the primary slip system of reinforcing crystals to improve the twinning propensity thus favoring the martensitic transformation.…”
Section: Metallic Glass Compositesmentioning
confidence: 99%
“…Similar results are traditionally obtained with fully crystalline shape memory materials, thus confirming the validity of the techniques for BMGs. In fact, Wu et al 21 found a few years later that promoting twinning of the reinforcing crystals present in BMGs through microalloying can improve the ductility of the BMGC similarly to that detected in microalloyed nanocrystalline materials. 22,23 Microalloying technology can be also used to tailor the structure of the amorphous phase and thus control the mechanical performance of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erosion resistance of martensite is superior to that of austenite [15], which can explain the interest in promoting the formation of martensite. An efficient method to do that is doping (i.e., microalloying) using elements such as Fe, Co and Ni because when added in the proper concentrations they can decrease the stress for transformation of CuZr austenite into CuZr martensite [16,17]. As a result, BMG composites with CuZr martensite phase embedded in the amorphous matrix are of interest to enhance the wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The easy nucleation and rapid propagation of shear bands can induce catastrophic fracture with very limited ductility, [15][16][17][18][19][20] impeding the further applications of BMGs. The fabrication of BMG matrix composites with ductile crystalline metal as reinforcement materials has yielded improvements in mechanical behavior [21][22][23][24][25][26][27][28] ; e.g., the in situ dendrite/BMG matrix composites exhibit increased both tensile and compressive strains to failure. [22][23][24][25][26][27][28] Previous studies [22][23][24] have pointed out that the ductile crystalline phase in the BMG matrix composite may have a dual role in the response of mechanical loading; they may serve as heterogeneous sites for the initiation of individual shear bands, while at the same time act as attraction or pinning centers during shear band propagation.…”
Section: Introductionmentioning
confidence: 99%